Voluntary blood donation knowledge, attitude, and practice among adult populations of Hosanna Town, South Ethiopia: a community-based cross-sectional study - Mussema, Abdulhakim; Bawore, Solomon Gebre; Abebaw, Tewodros; Tadese, Wegayehu; Belayineh, Melsew; Yirga, Abel; Mohammed, Tofik; Seid, Abdurezak Mohammed (Frontiers in Public Health, 2023)
Introduction: The demand for blood is increasing in all parts of the world, but availability of sufficient safe blood is a major challenge, especially in developing world. An adequate blood supply can only be assured through voluntarily blood donation. There is inadequate information on the level of blood donation practice in our community. This study aimed to assess the knowledge, attitude, practice and associated factors toward voluntary blood donation among hosanna town adult populations. Methods: A cross-sectional study was done from May 1, 2022, to June 30, 2022, on a total of 422 adult populations of Hosanna town. A simple random sampling technique was used to select the study subjects. Data were collected by face-to-face interviews using a structured pre-tested questionnaire. The levels of knowledge, attitude, and practice of participants toward blood donation were measured using a set of questions. Data was analyzed using SPSS version 25. Chi-square and odds ratios were calculated and results were presented with words and tables. Results: In this study, a total of 422 participants participated with a response rate of 96.6%. Of the total respondents, 204(48.3%), 209(49.5%), and 123(29.15%) study participants had good knowledge, favorable attitude, and experience of blood donation, respectively. Participants’ sex being male, and having favorable attitudes were found significant associations with blood donation practice. Male study participants were found more than two and a half times more likely to donate blood than females (AOR: 2.53; 95% CI: 1.54, 4.15). Those who had favorable attitudes were found more than three and a half times more likely to donate blood than those having unfavorable attitudes (AOR: 3.54; 95% CI: 1.32, 9.46) Conclusion and recommendations: A large proportion of adult populations had poor knowledge, unfavorable attitudes, and low practice toward volunteer blood donation. Therefore, local and national blood banks and transfusion agencies should design strategies to improve the adult population’s knowledge or the attitude of the adult population and motivate the populations to donate blood voluntarily.